2017
DOI: 10.22159/ijpps.2017v9i5.17721
|View full text |Cite
|
Sign up to set email alerts
|

V. Negundo, L. Camara and B. Variegata Plants Leaf Extract Exhibit Considerable in Vitro Antioxidant and Anticancer Activities

Abstract: Objective: The study was planned to investigate antioxidant and anticancer activities with the preliminary phytochemical analysis of methanolic extracts of Vitex negundo (V. negundo), Lantana camara (L. camara) and Bauhania variegata (B. variegata) plants leaf extracts. Methods:Phytochemical evaluation was performed for all the extracts, as per the standard methods. In vitro antioxidant activities were performed by using DPPH (2,2-Diphenyl-1-Picrylhydrazyl), ABTS (2, 2'-Azino-Bis-3-Ethylbenzothiazoline-6-Sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a recent study, they have also got the similar results [36]. In a similar study, methanolic extract of Lantana camara showed minimum IC 50 value for DPPH assay (48.75±2.34 µg/ml) [37].…”
Section: Discussionmentioning
confidence: 55%
“…In a recent study, they have also got the similar results [36]. In a similar study, methanolic extract of Lantana camara showed minimum IC 50 value for DPPH assay (48.75±2.34 µg/ml) [37].…”
Section: Discussionmentioning
confidence: 55%
“…Traditional plants are an important source of a natural remedies and remain to be broadly used to treat many diseases [18]. An infusion of the leaf and juice of the fruit is diuretic, and flower is said to have stimulant properties.…”
Section: Traditional Uses Of D Repensmentioning
confidence: 99%
“…On hydrogenation on PtO 2 , these compounds furnished dioxolanones 477e479 whose acid hydrolysis permitted the isolation of 480e482, side chains of deoxyHT (5), homodeoxyHT (22), and nordeoxyHT (21), respectively. When 453 was alkylated with benzyl bromide, the same sequence allowed the obtention of 483, the side chain of neoHT (19).…”
Section: Tietze's Synthesis (2005)mentioning
confidence: 99%